Assessment of Renal and Liver Function Tests Before and After Induction of Chemotherapy in Newly Diagnosed Acute Lymphoblastic Leukemia in Children (Community Based Medical Journal, 2022)
A prospective study was done in the Department of Paediatric Hematology & Oncology of Bangabandhu Sheikh Mujib Medical University (BSMMU), Dhaka, Bangladesh, between January and June of 2012, to observe the renal and liver function status in children suffering from acute lymphoblastic leukemia (ALL) before and after induction of chemotherapy. A total of 30 diagnosed patients of acute lymphoblastic leukemia were enrolled in the study. Renal and liver function tests were done before and after induction of chemotherapy. All the patients of the study were within 2-11 years range. Mean age was 5.12±2.53 years. Maximum 43.3% patients were within 3-6 years of age followed by 33.3% up to 3 years of age,13.3% within 6-9 year of age range and 10% above 9-year age range. 73.3% were male and 26.7% were female. Among the liver functions tests, mean bilirubin level of the patients before induction of chemotherapy was 2.31±4.71 mg/dl and after induction of chemotherapy was 1.12±2.15 mg/dl (P=0.122). Mean SGPT levels were 35.33±15.82 IU/L and 75±57.12 IU/l respectively (P=0.001). Mean total protein levels were 67.05±6.99 gm/dl and 64.47±7.51 gm/dl respectively (P=0.06). All the patients were HBsAg negative. Among the renal function tests, mean blood urea level of the respondents before induction was 28.89±7.95 mg/dl and after induction was 30.67±9.39 mg/dl (P=0.429). Mean serum uric acid levels were 4.63±1.18 mg/dl and 5.12±0.44 mg/dl respectively (P=0.044). Mean serum creatinine levels were 0.74±0.27 mg/dl and 0.67±0.22 mg/dl respectively (P=0.168). Mean GFR was 99.77±37.38 ml/1.732/min. before induction of chemotherapy and 108.57±37.29 ml/1.732/min. following chemotherapy (P=0.177). Kidney and liver functions may be affected in ALL in children. Recognition of hepatic and renal impairment at the onset of illness helps judicious chemotherapy in management of ALL.CBMJ 2022 January: vol. 11 no. 01 P: 21-26